El trabajo de los COA en el noroeste argentino - Tapia, Rebeca; Arias, Javier; Usandivaras, Felipe; Bernacki, David; Sánchez, Mariel (Revista Aves Argentinas, 2020)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).